Implementasi Kurikulum Merdeka Dalam Proses Belajar Mengajar di SMP Negeri 1 Kaliorang - Nur Aisyah; Faelasup Faelasup (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Abstract This study examines the implementation of teachers' teaching and learning process in the context of the Independent Curriculum at SMP Negeri 1 Kaliorang. As Indonesia's latest educational innovation, the Independent Curriculum aims to provide greater flexibility and autonomy to teachers and schools in managing learning. This study uses a qualitative approach with a case study method to deeply understand how teachers at SMP Negeri 1 Kaliorang adapt and apply the principles of the Independent Curriculum in their daily teaching practices. Data was collected through classroom observations, in-depth interviews with teachers and principals, and analysis of learning documents. The results show that teachers have begun integrating elements of the Independent Curriculum such as project-based learning, instruction differentiation, and formative assessment. However, there were also some challenges in implementation, including limited resources, the need for ongoing professional development, and the need for adaptation time.